2016
DOI: 10.1530/eje-15-1074
|View full text |Cite
|
Sign up to set email alerts
|

Polycystic ovary syndrome is associated with increased osteopontin levels

Abstract: Objective: Osteopontin (OPN) is a multi-functional secreted glycoprotein that plays a crucial role in glucose metabolism and inflammatory process. Growing evidence suggests that there is a link between OPN and ovarian function. However, no such link has yet been found for OPN in polycystic ovary syndrome (PCOS). Our aim was to ascertain whether circulating OPN levels are altered in women with PCOS and to determine whether OPN levels differ between the follicular phase and mid-cycle of the menstrual cycle in eu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
10
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 32 publications
(45 reference statements)
3
10
3
Order By: Relevance
“…In the present study, there was no significant difference in serum OPN levels between non-obese PCOS and control women. This finding is inconsistent with that of a recent study showing that PCOS is associated with increased serum OPN levels [ 33 ]. The major discrepancy may be due to the relatively low BMI and comparable HOMA-IR in our cohort.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…In the present study, there was no significant difference in serum OPN levels between non-obese PCOS and control women. This finding is inconsistent with that of a recent study showing that PCOS is associated with increased serum OPN levels [ 33 ]. The major discrepancy may be due to the relatively low BMI and comparable HOMA-IR in our cohort.…”
Section: Discussioncontrasting
confidence: 99%
“…We found that an increased circulating OPN level was more common in higher FAI groups and associated with high degree of FAI in non-obese PCOS patients. This finding is consistent with a recent study that showed that OPN levels are associated with free testosterone levels [ 33 ]. In the BMI subgroup analysis, OPN levels were significantly higher in the overweight PCOS group compared to the lean PCOS group, while this difference was not found in control women.…”
Section: Discussionsupporting
confidence: 94%
“…These results suggest that the presence of OPN at the endometrial surface is dependent on the expression of its receptor CD44 at the endometrial epithelial cell membrane. Interestingly, these findings agree with studies that reveal that interaction between CD44 and OPN represents a crucial ligand-receptor pair that facilitates systemic insulin resistance [36,37].…”
Section: Discussionsupporting
confidence: 90%
“…Despite speculative, it is likely that in healthy young women OPN does not reflect an increased CV risk (atherosclerosis is expected to be very initial), but rather a response to hormonal or environmental factors. [23][24][25][26] Conversely, the strong positive association between OPN and CCA-IMT observed in patients further indicates SLE as a surrogate of a more advanced CV disease independently of age. 27 In this context, OPN would act as an active proatherosclerotic factor, as previously suggested.…”
Section: Discussionmentioning
confidence: 98%
“…Furthermore, the characteristics of the study cohort we investigated young women (with SLE or healthy controls) might potentially explain the opposite association between OPN and CCA‐IMT observed in the two study groups. Despite speculative, it is likely that in healthy young women OPN does not reflect an increased CV risk (atherosclerosis is expected to be very initial), but rather a response to hormonal or environmental factors . Conversely, the strong positive association between OPN and CCA‐IMT observed in patients further indicates SLE as a surrogate of a more advanced CV disease independently of age .…”
Section: Discussionmentioning
confidence: 99%